Application of the American College of Cardiology (ACC/AHA) 2017 Guideline for the Management of Hypertension in Adults and Comparison with the 2014 Eighth Joint National Committee Guideline - AlAhmad, Mohammad (Journal of the Saudi Heart Association, 2021)
© 2021 Saudi Heart Association.